Controle de qualidade no plantio convencional e mecanizado de cana-de-açúcar - Carneiro, Tais Pereira de Oliveira [UNESP] (2015)
Brazil is the largest producer of sugarcane in the world, and the crop has broad relevance in the national agribusiness. Due to the importance of crop, it is essential to conduct a quality planting and improvements in the sector, since decisions taken now will have repercussions for the entire production cycle. Though the agricultural production system of sugarcane is heavily mechanized, the planting operation still requires technological advances. In this context, the objective was to assess the quality of the conventional planting operation (semi-mechanized) and mechanic sugarcane through statistical process control. Data were collected in the municipality of Monte Alto (SP), in area ceded by Usina São Carlos, with an area of 12 hectares for conventional system and 29 hectares for mechanized system, being collected 40 points in each treatment, in a total of 80 points, and each point owned 10 meters evaluation. Quality indicators evaluated were: total number of buds, number of viable buds,% viable buds, depth of plough, mating height and alignment, parallelism between planting lines, tillering at 30 and 60 days after sprouting. In the conventional system, the parallelism variables, tillering at 30 and 60 days showed greater variability, while for the number of viable buds and height of mating, these expressed stability for both planting systems